Correlation between homogenisation parameters and property evolution of AA3104 CBS after hot finish rolling - Lebakeng, Khethisa (Department of Mechanical Engineering, 2025)
AA3104 can-body stock (CBS) is produced through a series of thermomechanical processing stages, including direct chill (DC) casting, homogenisation, hot rough rolling, hot finish rolling, and cold rolling. Homogenisation is an important phase that controls the growth of intermetallic particles (IMPs) and dispersoids, affecting mechanical performance and texture evolution in following rolling stages. This study investigates the impact of different homogenisation procedures on the microstructure and mechanical properties of AA3104 during lab-scale hot rough rolling and plane strain compression (PSC) testing, which simulates hot finish rolling. Industry supplied DC-cast AA3104 ingot material was exposed to various homogenisation procedures at temperatures ranging from 500°C to 610°C to produce differences in IMP morphology and dispersoid dispersion within the structures. The homogenised samples were subjected to lab-scale hot rough rolling to achieve strain and IMP breakdown in line with that of industrial rough rolling. PSC testing on a Gleeble 3800 was utilised to simulate industrial hot finish rolling conditions. The microstructural evolution was investigated using light microscopy, scanning electron microscopy (SEM) in conjunction with energy-dispersive spectroscopy (EDS) and electron backscatter diffraction (EBSD) for grain and texture characterisation. The findings show that homogenisation temperature has a significant influence on IMP fragmentation, dispersoid refinement, which then has a marked effect on recrystallisation behaviour and texture development. The findings show that the 600°C/520°C condition resulted in coarse dispersoids (127 nm) with low number density (8.93 particles/µm²), the 560°C/520°C condition produced intermediate sized dispersoids (104 nm, 19.85 particles/µm²), and the 520°C condition generated fine, closely spaced dispersoids (56 nm, 55.92 particles/µm²). The cube texture intensity was found to increase with dispersoid density, with the 520°C sample displaying the strongest cube texture (~9.04), followed by 560°C/520°C (~7.5) and 600°C/520°C (~4.8). the 560°C/520°C homogenisation resulted in the largest recrystallised grains. While the 520°C homogenisation contained the finest dispersoids, the EBSD maps showed a fully recrystallised structure with recrystallised grains being smaller than the 560°C/520°C homogenisation. This is attributed to a combination of insufficient pinning pressure to fully retard recrystallisation as well as IMP topology effects on PSN and the overall recrystallisation kinetics, resulting in a smaller grain size than anticipated. There was no recrystallisation in the as-cast protocol, demonstrating that the dispersoids play an essential role in recrystallisation. None of the high temperature homogenisation practices resulted in sufficiently fine dispersoids to retard recrystallisation. These findings emphasise the significance of adjusting homogenisation parameters to alter microstructural features, such as IMPs and dispersoids for better hot rolling performance and final property and microstructural development. The findings do illustrate the importance of a more detailed interrogation of the role of these critical features in the rolling process. This should be achieved on a laboratory scale initially. The experimental protocol for this work used a fully lab scale simulation approach, which showed successful alignment with initial partial industrial samples. The microstructures of the 560°C/520°C material were compared to samples where only the finish rolling was simulated (on industrially supplied transfer bar after industrial homogenisation and rough rolling). The grain size and cube texture intensity of the two approach showed similarities in grain size and cube texture intensities. This indicates an equivalent thermomechanical processing route to achieve these similar microstructures. This is a successful first step in the validation of a full through process simulation of processing on a laboratory scale.